Sex and Reproduction in the Transmission of Infectious Uveitis - Janet L. Davis (Journal of Ophthalmology)
Current data permit only speculations regarding sex differences in the prevalence of infectious uveitis between women and men because uveitis case surveys do not uniformly report gender data. Differences in prevalence that are reported in the literature could relate to simple differences in the number of women and men at risk for infection or to biological differences between men and women. Compared to other types of uveitis, infectious uveitis may be directly related to occupational exposures or sexual behaviors, which differ between women and men, and may mask actual biological differences in susceptibility to ocular manifestations of the infection and its prognosis. In infectious uveitis for which there is no element of sexual transmission and data is available, prevalence of ocular disease is roughly equal between women and men. Women also have a unique relationship with infectious uveitis in their role as mothers. Vertical transmission of infections such as herpes simplex, toxoplasmosis, and cytomegalovirus can produce severe chorioretinitis in neonates.